Element of warranty of IBS structural system for construction industry - Sing, Annan Vessinuk (2013)
Industrialized building system (IBS) is the prefabrication and industrialized construction concept in Malaysia. It is famously around 20 century for the construction project. IBS is a building pre-cast component that done by manufactory and transport to the site for assembly to the construction project. In this country, any building after completion doesn’t have any warranty by developer or contractor even it’s used the IBS system. Its difference to the mechanical sector that it’s has a warranty for each component after purchased or even after the assembly. Nowadays, the construction sector had a life span for long time which is 50 years after the completion of the project. So, the study is conduct to create the warranty of IBS component for construction industry same as the mechanical sector and to estimate how the possible warranty period should gives for the IBS component in the construction in Johor, Malaysia by using a data collection from load test data by the laboratory experiment. According to the result and analysis, the warranty period for the IBS structure should be 15 to 20 years.